If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-8b-8)-1=39-8b
We move all terms to the left:
3(-8b-8)-1-(39-8b)=0
We add all the numbers together, and all the variables
3(-8b-8)-(-8b+39)-1=0
We multiply parentheses
-24b-(-8b+39)-24-1=0
We get rid of parentheses
-24b+8b-39-24-1=0
We add all the numbers together, and all the variables
-16b-64=0
We move all terms containing b to the left, all other terms to the right
-16b=64
b=64/-16
b=-4
| 7k=3-37 | | -29+7k=2(k-2) | | 2-5|5m-5}=-73 | | 100+4x=70+9x | | 5x+25=16x+80 | | -6(1+8x)-x=-104 | | 3x-15=x+4 | | 8(t-3)+4t=6(t+1)-10 | | 87=3+2(6x-6) | | (5-x)=10(20x-7) | | - x/3+21=14 | | -8.4-1.3k=-5.54 | | 2(5x-3)=26 | | -6y+5=5y+4 | | $2+3(z-3)=z+3z+6z$. | | x/5=13 | | 1/20=m+1/5 | | 32=4x+12x | | 5x+1=7-2 | | -10/3=2n-41/3 | | 8^3x=16^30 | | 0.012x+0.04=0.004 | | x+4.8=1.4x | | 5(3d+19)=5d | | 3x-31=(x+6)×2 | | g/6=22 | | M^2-2m-36=19 | | j-33=6 | | 3y-4=5y-8 | | 101.12=12.8v | | 6x+3=-3x+8 | | x-13=22.3 |